Non-uniform Rooftop PVs Distribution Effect to Improve Voltage Profile in Residential Feeder - Zamzami Zamzami; Nelly Safitri; Fauzi Fauzi (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
This paper presents the simple design of a grid-tied single-phase with distributed rooftop photovoltaic (PV) non-uniformly location and ratings. All the inclusion components in the developed scheme are estimated and defined as the inevitability of low voltage (LV) residential network. This developed scheme is purposed for allocating AC and DC load, which are divided into four steps: the sized determination of PV inverter (1-5kW), the selection of PV array, the size determination of battery and the selection of other supporting components. The purposed configuration consists of modeling the system with non-uniform distributions of rooftop PVs, modeling the rooftop PVs based on their injected active and reactive power, and finally the inclusion of battery storage, based on its state of charge (SOC). Due to test the configuration, several cases are built in the MATLAB platform. Simulation results have been generated and analyzed for an unbalanced three-phase residential feeder which is populated with rooftop PVs and battery storage (BS). The simulation results show that the unbalanced reduction due to the coordinate of PVs and BS that provided educated energy storage when the unequal loadings are there, have significant effect toward the anxiety of the distribution network are successfully done.